2021
DOI: 10.21037/apm-21-1788
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate medication discontinued or changed based on pharmacists’ recommendations in older end-stage cancer patients receiving palliative care: a cross-sectional study

Abstract: Background: Avoiding potentially inappropriate medications (PIMs) can reduce adverse events in older cancer patients receiving palliative care. However, studies have not examined the extent to which pharmacists' recommendations reduce the prescription of PIMs. Therefore, we designed a cross-sectional study to determine the extent to which their recommendations play a role in reducing the prescription of PIMs for older cancer patients receiving palliative care.Methods: Patients brought their medications with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Deprescribing is a complex process that requires a careful assessment of the benefits and harms for patients and requires shared decision-making between doctors, patients, and pharmacists, which is not always easy [ 4 , 12 , 18 , 21 , 22 , 26 ]. Frequent and systematic re-evaluation of the adequacy and safety of the prescription over time- as well as the appropriateness and effective cessation- are required [ 3 , 13 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deprescribing is a complex process that requires a careful assessment of the benefits and harms for patients and requires shared decision-making between doctors, patients, and pharmacists, which is not always easy [ 4 , 12 , 18 , 21 , 22 , 26 ]. Frequent and systematic re-evaluation of the adequacy and safety of the prescription over time- as well as the appropriateness and effective cessation- are required [ 3 , 13 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24] Few studies were conducted in inpatients settings, although hospitalized patients may be fragile, with acute conditions or cancer progression. [25][26][27] Deliens et al reported the only comprehensive intervention at both admission and discharge in a geriatric oncology unit, in 91 patients ≥70 years. 25…”
Section: Introductionmentioning
confidence: 99%
“…In previous evaluations of pharmaceutical care interventions in older patient with cancer, pharmacists identified DRPs in up to 95% of patients and enabled the resolution of up to 40% of DRPs 20–24 . Few studies were conducted in inpatients settings, although hospitalized patients may be fragile, with acute conditions or cancer progression 25–27 . Deliens et al reported the only comprehensive intervention at both admission and discharge in a geriatric oncology unit, in 91 patients ≥70 years 25 .…”
Section: Introductionmentioning
confidence: 99%